The Effects of Exercise and Agility on Dribble (Skills) of Basketball Extracurricular Participants in SMPN 10 Bengkulu - Afrilliyan, Arrendi; Pramono, Harry; Soenyoto, Tommy (Journal of Physical Education and Sports, 2018)
The aim of this research is to identify and analyze: (1) the difference in effects of two ball dribble and dribble of the wall exercise method on the dribble skills of basketball extracurricular participants in SMPN 10 Bengkulu, (2) the difference in the effects of participants’ different agility level on the dribble skills of basketball extracurricular participants in SMPN 10 Bengkulu, (3) interaction between exercise methods and agility level on the dribble skills of basketball extracurricular participants in SMPN 10 Bengkulu. This research uses experimental methodology with 2x2 factorial design. Data analysis technique uses Analysis of Varian (ANOVA) with significance level (α) 0.05. Independent variables are two ball dribble exercise method and dribble of the wall exercise method. Attributive variables are high and low agility and its dependent variable is dribble skills. The findings are: (1) there is a significant effect difference between two ball dribble exercise method and dribble of the wall exercise method on basketball dribble skills with p (.049) < a (0,05), and Ftest (4.37) > Ftable (4.04), (2) there is an effect difference on basketball dribble skills between participants with high agility and participants with low agility, with p (.003) < a (0.05), and Ftest (11.42) > Ftable (4,04), (3) there is an interaction between exercise methods and agility levels on basketball dribble skills with p (.030) < a (0.05), and Ftest (9.64) > Ftable (4.04).